Prevalence and Associated Factors of Iron Deficiency and Iron Deficiency Anemia Among Under-5 Children: A Systematic Review and Meta-Analysis - Solomon Gedfie MSc; Solomon Getawa MSc; Mulugeta Melku MSc (SAGE Publishing, 2022)
Background. Iron deficiency anemia is a common health problem that affects children under the age of five. Children's cognitive performance is impaired by iron deficiency, which impacts their psychomotor development. Therefore, the aim of this study was to determine the global prevalence and associated factors of iron deficiency and iron deficiency anemia among under-5 children. Methods. Relevant publications published till March 30, 2021 were identified in databases such as Medline/PubMed, Science Direct, Popline, EMBASE, African Journals Online, Scopus, and Google Scholar. The STATA version 11 software was utilized for the analysis. To determine the level of heterogeneity, I 2 test statistics were used. To detect publication bias, funnel plots analysis and the Egger weighted regression test were used. Results. The global pooled prevalence of iron deficiency anemia and iron deficiency was 16.42% (95% CI: 10.82, 22.01) and 17.95% (95% CI: 13.49, 22.41), respectively. Age less than 2 years (OR = 1.26; 95% CI: 1.14, 1.38) and living in a large family size (OR = 1.38; 95% CI: 1.18, 1.58) were associated with iron deficiency anemia. Children born from anemic mother, low birth weight, and do not drink iron fortified milk (OR = 1.20; 95% CI: 1.05, 1.36), (OR = 1.15; 95% CI: 1.01, 1.36) and (OR = 1.28; 95% CI: 1.10, 1.46), respectively were associated factors of iron deficiency in under-5 children. Conclusion. The prevalence of iron deficiency anemia and iron deficiency was significant across the globe, particularly in Asia and Africa. Therefore, regular screening and treatment of iron deficiency and iron deficiency anemia are required especially in high-risk children to reduce their complication. PROSPERO registration number: CRD42021267060